A beginner's guide to New Testament studies : understanding key debates - Nijay K. Gupta (Grand Rapids, MI : Baker Academic, a division of Baker Publishing Group, 2020)
"This accessible and balanced introduction to key questions in New Testament studies fairly presents the spectrum of viewpoints on debated topics"-- Provided by publisher
Keywords: Bible; Criticism, interpretation, etc; Bible. New Testament Criticism, interpretation, etc